Pengaruh Kualitas DIPA dan Akurasi Perencanaan Kas Terhadap Kualitas Penyerapan Anggaran - Heru Suwito (Jurnal Akuntansi dan Keuangan (JAK), 2018)
Goverment faces economic problem continuously that affect the economic growth where the most impact occured is from State Budge. The low absorption rate of goverment budget as seen from the realization of the state ministry/institutional budget hampers the rate of economic growth. The purpose of this study is to provide empirical evidence about the effect of DIPA quality and the accuracy of cash planning on the level of budget absorption of working unit in the working area of regional office of the Directorate General of Treasury, Lampung Province. The data used is secondary data in the form of data from the spending units which revised the budget and data on the planned withdrawal of the budget in the regional office of the Directorate General of Treasury, Lampung Province in 2013-2016. The sample of this study are working units who managed a budget of more than 10 billion on a quarterly basis during the period 2013-2016, with a total sample of 496 data studies. Hypothesis testing is performed using panel data regression Eviews version. The results of the study show that the quality of DIPA and accuracy of cash planning have a significant positive effect on the level of budget absorption of working units in the working area of regional office of the Directorate General of Treasury, Lampung Province.